THE INFLUENCE OF MASS ON VELOCITY AND ACCELERATION BASED ON NEWTON’S SECOND LAW BY USING LINIER AIR TRACK - Ratni Sirait (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
The research aims to see whether there is influence of distance on time, mass effect on velocity, and mass effect on acceleration. Variables in this study consisted of manipulation variables of load and distance mass, response variables i.e. time taken and moving load velocity. The results showed that the effect of distance to time can be seen from the correlation coefficient value R2 = 0.999 for the mass of 128 g and 400.46 g which means that there is influence of 99.9%. And there is the effect of mass on the velocity and acceleration that is the velocity and acceleration of the load mass of 128 g of 0.062 m/s and 0.00625 m/s2 greater than the velocity and acceleration with mass load 400.46 g of 0.056 m/s and 0.0518 m/s2. It is proven by Newton's law of velocity and acceleration is inversely proportional to mass, meaning that the greater the load mass, the speed and acceleration of the object will be smaller, and vice versa. Keywords: Acceleration, linier air track, load mass, Newton’s second law, and velocity.